Effects of Morphine Added to Bupivacaine in Ultrasound - guided Transversus Abdominis Plane Block for Inguinal Hernia Repair Under Spinal Anaesthesia: A Randomized Double Blind Study - Gurung, Purna Kala; Sah, Birendra Prasad; Shrestha, Vijay (Journal of BP Koirala Institute of Health Sciences, 2025)
Background: The transversus abdominis plane (TAP) block is an easy-to-perform and effective peripheral abdominal field block that has gained popularity as part of a multimodal analgesic regimen. The aim of this study was to determine the analgesic effects of morphine added to bupivacaine in a TAP block for inguinal hernia repair. Methods: Forty adult patients with ASA PS I–II scheduled for elective inguinal hernia surgery under spinal anaesthesia were randomized to undergo ultrasound-guided USG) TAP block with 20 ml of 0.25% bupivacaine (group B) versus 20 ml of 0.25% bupivacaine with 3 mg morphine (group BM). Patients were followed for 24 hours postoperatively for rescue analgesics consumed, duration of analgesia, NRS scores at rest and on cough, and adverse effects. Results: The median (IQR) duration of analgesia in minutes of group B 385(248.75-825) and group BM 761(248.75-1440) were statistically non-significant (p > 0.05). The median (IQR) rescue analgesics tramadol consumed were 50 (50-50) mg in group B and 50 (0-50) mg in group BM (p > 0.05). There were no significant differences in NRS scores at rest and on cough at 0 and 4 hour, but were significantly less in group BM than group B at 8 and 24 hour (p < 0.05). Conclusions: The addition of morphine to bupivacaine in USG TAP block failed to show significant analgesic effects than bupivacaine alone in terms of duration of analgesia and total analgesic consumed, but a significantly lower pain score was observed in group BM than group B at 8 and 24 hr.